\(a,VT=ab-ac+ac-bc=ab-bc=b\left(a-c\right)=VP\\ b,VT=ab-ac-ab-bc=-ac-bc=\left(a+b\right)\left(-c\right)=VP\)
\(a,VT=ab-ac+ac-bc=ab-bc=b\left(a-c\right)=VP\\ b,VT=ab-ac-ab-bc=-ac-bc=\left(a+b\right)\left(-c\right)=VP\)
Biến đổi vế trái thành vế phải:
a(b + c) - b(a - c) = (a + b)c
Biến đổi vế trái thành vế phải :
a) a ( b + c ) − b ( a − c ) = ( a + b ) . c ;
b) ( a + b ) ( a − b ) = a 2 − b 2 .
Biến đổi vế trái thành vế phải:
a(b + c)(a - b) = (a + b)c
Biến đổi vế trái thành vế phải : a, a.(b-c)+c.(a-b) = b.(a-c) b, (a+b) .(c+d) -(a+d) .(b+c) = (a-c) .(d-b)
Biến đổi vế trái thành vế phải:
a) a + b 2 = a 2 + 2 a b + b 2
b) ( a − b ) ( a + b ) = a 2 − b 2
c) a ( b + c ) − b ( a − c ) = ( a + b ) c
Biến đổi vế trái thành vế phải
a .(b + c) - b .(a - c) = (a + b ) . c
biến đổi vế trái thành vế phải:
( a + b )( c + d ) - ( a + d )(b + c ) = ( a - c )( -b + d )
Biến đổi vế trái thành vế phải:
a(b-c)+c(a-b)=b(a-c)
Biến đổi vế trái thành vế phải
a) a.(b+c) - b.(a-c) =(a+b).c
b)(a+b).(a-c) =\(a^2-b^2\)